2020
DOI: 10.1007/s00107-020-01525-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on thermal properties of European beech wood

Abstract: Beech wood, due to its properties, is one of the most versatile and successfully used construction materials. The wood properties could even be improved, and among different wood modification processes, the thermal modification approach is usually considered as an environment-friendly technology based only on the heat and water application during wood treatment. Changes in material properties resulting from the thermal treatment of wood increase applicability of this material, but on the other hand, detailed k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…7. The thermal conductivity of pine and beech were 0.12 and 0.23 W m −1 K −1 , 1 respectively, which were in line with the reported values in the literature [38,39]. Previous studies [38] discussed that thermal conductivity of wood materials varies with density, moisture content and wood species.…”
Section: Thermal Conductivity Measurement With Heat Flow Metersupporting
confidence: 88%
See 1 more Smart Citation
“…7. The thermal conductivity of pine and beech were 0.12 and 0.23 W m −1 K −1 , 1 respectively, which were in line with the reported values in the literature [38,39]. Previous studies [38] discussed that thermal conductivity of wood materials varies with density, moisture content and wood species.…”
Section: Thermal Conductivity Measurement With Heat Flow Metersupporting
confidence: 88%
“…The thermal conductivity of pine was reported to be in the range 0.1-0.14 W m −1 K −1 , depending on the species. Czajkowski et al [39] studied thermal conductivity of beech and reported a value of 0.24 W m −1 K −1 along the radial direction, while other study [38] reported a value of 0.19 W m −1 K −1 . These studies corroborate the funding of the present study.…”
Section: Thermal Conductivity Measurement With Heat Flow Metermentioning
confidence: 99%
“…When studying the influence of thermal treatments on the wood of different clones of Eucalyptus urophylla x Eucalyptus grandis, JUIZO et al [31] obtained ML varying from 17 to 22% employing a temperature of 200 °C for 4 h in a laboratory kiln. According to CZAJKOWSKI et al [32], ML is due to the thermal degradation of cellulose, hemicelluloses and lignin, as well as the volatilization of some extractives.…”
Section: Discussionmentioning
confidence: 99%
“…Another wood modification method that gaining in popularity over the last decades is heat treatment. Heat treatment is an environmentally friendly method applied without using any chemicals to improve the properties of wood material [5,15]. When wood is heated, generally chemical changes start to take place inside the wood structure depending on some conditions (treatment temperature, treatment time, atmosphere, etc.…”
Section: Introductionmentioning
confidence: 99%